Race as a prognostic factor of breast mucinous carcinoma - Dingyuan Wang; Yang Wang; Songlin Gao; Rongshou Zheng; Guijian Wu; Jianping Wang; Can Lu; Kena Bu; Chun Zhang; Wanqing Chen; Bailin Zhang (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose The rarity of breast mucinous carcinoma (BMC) makes it challenging to study the prognosis of this disease across diverse racial populations. This study aimed to leverage epidemiological data on immigrant populations to elucidate the prognostic differences in BMC patients from various racial/ethnic backgrounds. The goal was to help formulate more personalized clinical practice guidelines for the management of this rare malignancy. Methods The study included 208 BMC patients from China and 10,322 BMC patients from the SEER database. Clinicopathological data, treatment information, and survival outcomes were compared across different racial/ethnic groups using statistical analyses. Results Asian American BMC patients were younger at diagnosis and had more favorable tumor grade and stage compared to other racial groups. After adjusting for clinicopathological factors and treatments, Asian American BMC patients exhibited significantly better overall survival (OS) than black (HR = 1.53, 95% CI: 1.05–2.22, P = 0.027) and white patients (HR = 1.41, 95% CI: 1.03–1.94, P < 0.001). Specifically, non-Chinese American patients had a worse OS compared to Chinese patients (adjusted HR = 2.59, 95% CI: 1.15–5.83, P = 0.022). Chemotherapy significantly improved OS only in black BMC patients (adjusted HR = 0.52, 95% CI: 0.27–0.98, p = 0.045), but not in other racial/ethnic groups. Conclusion Race is an independent prognostic factor for BMC. Compared with Chinese patients, black and white American patients have a worse prognosis in terms of OS. Treatment guidelines for BMC patients should be formulated with considerations of race factors. For patients with BMC originating from China, a more conservative treatment approach may be warranted.